Isoflavones and Isoflavone Glycosides: Structural-Electronic Properties and Antioxidant Relations—A Case of DFT Study - Son Ninh The; Thanh Do Minh; Trang Nguyen Van (Journal of Chemistry)
Isoflavonoids and isoflavonoid glycosides have drawn much attention because of their antioxidant radical-scavenging capacity. Based on computational methods, we now present the antioxidant potential results of genistein (1), biochanin A (2), ambocin (3), and tectorigenin 7-O-[β-D-apiofuranosyl-(1-6)-β-D-glucopyranoside] (4). The optimized structures of the neutral and radical forms have been determined by the DFT-B3LYP method with the 6-311G(d) basis set. From the findings and thermodynamic point of view, the ring B system of isoflavones is considered as an active center in facilitating antioxidant reactions. Antioxidant activities are mostly driven by O-H bond dissociation enthalpy (BDE) following hydrogen atom transfer (HAT) mechanism. Antioxidant ability can be arranged in the following order: compounds (4) > (3) > (2) > (1). Of comprehensive structural analysis, flavonoids with 4′-methylation and 6-methoxylation, especially 7-glycosylation would claim responsibility for antioxidant enhancement.